Experimental and Numerical Studies on the Compressive Strength Test of Recycled Aggregate Concrete using Digital Image Correlation - Sentosa, Bastian Okto Bangkit; Ferdinand, Joshua; Handika, Nuraziz (Makara Journal of Technology, 2024)
The utilization of recycled aggregate (RA) as substitute of natural aggregate in concrete contributes to the research of sustainable building construction materials. Many applications of RA have been studied worldwide. However, the application of RA with a specific range of strength and specific damage behavior requires further study. This research aims to examine the mechanical characteristics of RA concrete, particularly its load–displacement response and crack pattern, through the experimental and numerical studies of compressive strength test. Laboratory concrete waste from cylindrical sample with 30–35 MPa strength was chosen as RA. The digital image correlation (DIC) method was applied throughout the compressive tests. In the post-processing step of the DIC method, vertical and horizontal displacement and the strains of the observed concrete surface were predicted to detect the crack patterns at the initial and maximum load stages. Numerical modeling was then performed on the same shape by applying the concrete damage model by Mazars. Numerical modeling gives close results to the experimental ones from the initial stage to the maximum load stage. These results can be useful for further studies to improve the accuracy of numerical models for alternative building material, specifically for large structures.